2010
DOI: 10.1136/sti.2009.038356
|View full text |Cite
|
Sign up to set email alerts
|

Lot quality assurance sampling for monitoring coverage and quality of a targeted condom social marketing programme in traditional and non-traditional outlets in India

Abstract: ObjectivesThis study reports on the results of a large-scale targeted condom social marketing campaign in and around areas where female sex workers are present. The paper also describes the method that was used for the routine monitoring of condom availability in these sites.MethodsThe lot quality assurance sampling (LQAS) method was used for the assessment of the geographical coverage and quality of coverage of condoms in target areas in four states and along selected national highways in India, as part of Av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 14 publications
2
24
0
1
Order By: Relevance
“…Other studies have found similar results supporting the claim that the condom supply was increased by Avahan [20]. The increase in peer educators as the source of condom by FSWs reported during the IBBA validated the CMIS condom distribution data.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Other studies have found similar results supporting the claim that the condom supply was increased by Avahan [20]. The increase in peer educators as the source of condom by FSWs reported during the IBBA validated the CMIS condom distribution data.…”
Section: Discussionsupporting
confidence: 78%
“…Free condoms distributed to FSWs by the program were tracked yearly from the Avahan CMIS and annual condom sales data from the condom social marketing program [20] in Maharashtra. Data on the reported sources of obtaining condom last time from IBBA were used to validate trends from the CMIS.…”
Section: Methodsmentioning
confidence: 99%
“…Exposure to media based communication on STIs and condom use was found to be a significantly associated with condom use; the studies by Lipovskey 13 , Suryawanshi 21 that evaluated condom use among clients who were exposed to media interventions reported condom use. A meta-analysis of the effect of social marketing efforts on condom use 22 also found increased likely hood of condom use; the interventions for clients of FSWs in the states sampled in IBBA were a combination of social marketing of condoms and media based campaigns 13,23 ; given the rigorous methodology of IBBA, the findings from the current analysis add to the evidence base for the efficacy of social marketing efforts.…”
Section: Discussionmentioning
confidence: 76%
“…For example, Mechai Viravaidya's CBO, Population Development Association, raises money through revenue-maximizing businesses (e.g., restaurant and resort) which is then re-invested in family planning services and condom promotion, a model that has been recognized as a UNAIDS best practice [ 17 ]. Another example of SESH is social marketing to enhance uptake of condoms among sex workers, an approach that was found highly effective as part of the Avahan Initiative in India [ 18 ]. Social entrepreneurship models have slowly gained acceptance in a number of public health fields [ 19 ],[ 20 ], but are particularly important in sexual health where point-of-care tests are increasingly affordable and available.…”
Section: Introductionmentioning
confidence: 99%